The impact of fungi in increasing essential oils and chemical components of agarwood (Gyrinops versteegii) - I MADE MEGA; NI LUH KARTINI; I GEDE SURANJAYA; IDA BAGUS PUTU BHAYUNAGIRI; MADE SRI SUMARNIASIH; I NENGAH SURATA ADNYANA (Society for Indonesian Biodiversity, 2024)
Abstract. Mega IM, Kartini NL, Suranjaya IG, Bhayunagiri IBP, Sumarniasih MS, Adnyana INS. 2024. The impact of fungi in increasing essential oils and chemical components of agarwood (Gyrinops versteegii). Biodiversitas 25: 2552-2559. Essential oil, a key agarwood process product, is the fundamental ingredient in perfume, cosmetics, and drugs. The type of agarwood plant, the induction microbes, and the environmental factors influence the production of essential oil in agarwood. This research, characterized by its rigorous application of a randomized block design (RBD) experimental design and statistical analysis, aims to analyze the agarwood essential oil content and chemical components upon applying three fungal inoculants. The treatments applied are: (i) Trichoderma harzianum inoculant, (ii) Fusarium solani inoculant, (iii) Rhizopus microsporus inoculant, and (iv) Control (without fungal inoculant). Each treatment had 15 repetitions. The parameters observed are agarwood color, scent, essential oil content, and chemical components. The quantitative observation data was statistically analyzed by variance analysis, and if a significant value was found, the analysis was followed by the Least Significant Difference Test (5% level). The results showed that the type of fungal inoculant applied significantly influences the essential oil content in the wood. The highest essential oil content of 0.7413 mL/kg was obtained by applying Fusarium solani fungal inoculant. The lowest 0.5249 mL/kg content was obtained in the control treatment (without fungi). The chemical components of essential oils are Butanoic acid, 3,7-dimethyl, 2,6-octa diethyl, Hexadecanoic acid, and methyl ester. Citronelol; Beta Citranelol; 3,7-dimethyl-2,6-octadien-l-ol; Citronellol acetate; Citral; Geranyl acetate; 2,6,10_Dodecatrien-1-ol, 3,7,11-trimethyl (Farnesol); Selina-6-en-4-ol; and (-)-Globulol.